Comparison of Penile Prosthesis Cultures Within Individual Patients After Removal/Replacement and Subsequent Salvage. Issue 4 (14th July 2020) - Chandrapal, Jason; Harper, Shelby; Davis, Leah G.; Lentz, Aaron C.
Abstract: Introduction: Infection rates for virgin inflatable penile prostheses (IPPs) range from 1 to 3%; however, this can increase to 7–18% after IPP revision or removal/replacement (RR) for mechanical malfunction. Although studies have reported various RR and salvage cultures, limited data are available that directly compare microorganisms after each of these procedures within the same patient. Comparison of these cultures may determine if the infection is due to a persistent microorganism or new inoculation. Aim: Our aim is to characterize prosthesis cultures within individual patients who develop infection after RR. Methods: We retrospectively reviewed patients undergoing various IPP procedures at our institution from September 2002 to August 2018. RR procedures were determined by current procedural terminology codes 54, 410 or 54, 416. Infection, defined as salvage or explantation without replacement for infectious reasons, was described by current procedural terminology codes 54406, 54411, 54415, or 54417. Inclusion criteria consisted of IPP infection after RR and the presence of both RR and salvage cultures within the same patient. Owing to the small cohort size, only descriptive statistics were used. Main Outcome Measures: Characterization of removal/replacement and salvage cultures is the main outcome measure of this study. Results: A total of 202 non-infected RR procedures were performed with 9 cases (4%) of IPP infection after RR identified. Four (44%) of the RR cultures were positive and contained gram-positive (44%) and gram-negative (11%) organisms. In comparison, salvage cultures grew gram-positive bacteria (66%), gram-negative bacteria (33%), and/or fungal elements (33%). A direct comparison of the RR and salvage cultures indicated that only 2 patients (22%) grew similar organisms. Conclusions: The risk of IPP infection after RR and modified washout is low. In this small series, gram-positive bacteria were most common at the time of RR and salvage. The increased incidence of fungal infections may indicate a need to modify RR protocols. Larger multi-institutional studies are needed to further investigate this relationship. Chandrapal J, Harper S, Davis LG, et al. Comparison of Penile Prosthesis Cultures Within Individual Patients After Removal/Replacement and Subsequent Salvage. Sex Med 2020;8:783–787.